INOVASI PELAKSANAAN PROGRAM JATIM BEJO DALAM PENGEMBANGAN UMKM JAWA TIMUR MELALUI PEMASARAN DIGITAL - Rafif Farrell Nawwardy Ubadah, Sadina (LPPM STISIP IMAM BONJOL, 2025)
The innovation in implementing the Jatim Bejo Program represents a strategic initiative by the East Java Provincial Government to support the development of Micro, Small, and Medium Enterprises (MSMEs) through digital marketing. In the context of digital transformation, MSMEs face significant challenges related to changing consumer behavior and technological advancements. This program aims to enhance the competitiveness of MSMEs by providing training, creating a digital ecosystem, and leveraging data analytics for more targeted marketing. Known for its emphasis on local wisdom and cross-sector collaboration, Jatim Bejo not only facilitates access to modern technology but also helps MSMEs maintain their local identity in product marketing. Through the implementation of supportive policies and regulations, the Jatim Bejo Program is expected to significantly impact regional economic growth and strengthen the sustainability of MSMEs in the digital era.